1999
DOI: 10.1152/ajpendo.1999.276.1.e125
|View full text |Cite
|
Sign up to set email alerts
|

Endothelium removal induces iNOS in rat aorta in organ culture, leading to tissue damage

Abstract: After endothelial damage in vivo, there is an induction of nitric oxide synthase (NOS) in the underlying smooth muscle cells. We hypothesized that intrinsic factors could induce NOS independently of blood elements. This was tested using an in vitro organ culture technique. Rat aortas with endothelium removed before 24-h organ culture (ERB) failed to constrict to phenylephrine after culture, whereas with endothelium removal after culture there was a normal constrictor response. Constrictor activity in ERB aorta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
13
1

Year Published

2000
2000
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 50 publications
(48 reference statements)
3
13
1
Order By: Relevance
“…This appears similar to therapeutic strategies adopted in animal models and in humans with septic shock. In such models the induction of iNOS, following endothelial damage (Binko et al 1999), in vivo endotoxin injection (Kelly et al 1996), or activation of pro-inflammatory cytokines (Finkel et al 1992) with consequent generation of large amounts of NO, is responsible for a reversible defect in myocardial function (Vallance et al 2000).…”
Section: Nitric Oxide and The Frank-starling Responsementioning
confidence: 99%
“…This appears similar to therapeutic strategies adopted in animal models and in humans with septic shock. In such models the induction of iNOS, following endothelial damage (Binko et al 1999), in vivo endotoxin injection (Kelly et al 1996), or activation of pro-inflammatory cytokines (Finkel et al 1992) with consequent generation of large amounts of NO, is responsible for a reversible defect in myocardial function (Vallance et al 2000).…”
Section: Nitric Oxide and The Frank-starling Responsementioning
confidence: 99%
“…This difficulty can be overcome by incubation of intact segments. Incubation of aortic segments produces a decrease in phenylephrine-evoked contraction that is restored by NOS inhibition or glutathione (Binko et al, 1999) and stimulates nitrate production that is blocked by N G -nitro-L-arginine methyl ester (L-NAME) (Bishop-Bailey et al, 1997).…”
Section: Introductionmentioning
confidence: 99%
“…Oxidative stress was indirectly evaluated by measuring anti-oxidant capacity: glutathione-related (glutathione Stransferases (GSTs, EC 2.5.1.18), glutathione peroxidase (GPX, EC 1.11.1.9), glutathione reductase (GSSR, EC 1.6.4.2) and catalase (EC 1.11.1.6) activity. The impact of oxidative stress on vasomotion was assessed by co-incubation with the anti-oxidants reduced glutathione (GSH) (Binko et al, 1999) or pyrrolidine dithiocarbamate (PDTC) (Moellering et al, 1999). The role of iNOS was appraised by measurement of iNOS mRNA expression (compared to cyclo-oxygenase (COX-2) expression) and the impact of L-NAME on contraction.…”
Section: Introductionmentioning
confidence: 99%
“…14,15 Oxidative stress Similar to other published studies, no immunohistochemical expression of nitrotyrosine in the venous wall was observed. 11,12 NO can react with the superoxide anion (O 2 − ) to produce peroxynitrite (ONOO − ), 20 which can cause nitration of tyrosine residues in proteins. Therefore, the absence of nitrotyrosine staining provides indirect evidence that oxidative stress does not have a crucial role.…”
Section: Tissue Nitrite/nitratementioning
confidence: 99%